The Role of Students in Practicing Pancasila Values in the Era of Globalization - Anggreini, Maya; Joshua, Wang; Maharjan, Kailie (International Journal of Educational Narratives, 2023)
Background. Students are one of the most important assets for the Indonesian nation in the nation-building period, meaning that it is important to have a student's role in national development. Purpose. The purpose of this paper is to describe the role of.The results of this paper give birth to the roles of students in practicing Pancasila values in the era of globalization. Method. The study involved 288 university students from Chinese, Japanese, and Korean TFL settings, and the data from questionnaires were analysed using appropriate statistical methods. Results. Pancasila values that have been agreed upon as good values that must be instilled in each soul of the Indonesian people.The next hope is that the understanding of Pancasila values to the people can provide a strong mental firmness so that it is not easily influenced by cultures that may be contrary to the culture of noble heritage. Conclusion. Therefore, it is very necessary for Pancasila Education to be taught to the nation's children.